2021
DOI: 10.3390/ijerph18168431
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Clustering in Non-Cystic Fibrosis Bronchiectasis Patients: The Role of Eosinophils in Disease Severity

Abstract: Whether high blood eosinophil counts may define a better phenotype in bronchiectasis patients, as shown in chronic obstructive pulmonary disease (COPD), remains to be investigated. Differential phenotypic characteristics according to eosinophil counts were assessed using a biostatistical approach in a large cohort study from the Spanish Online Bronchiectasis Registry (RIBRON). The 906 patients who met the inclusion criteria were clustered into two groups on the basis of their eosinophil levels. The potential d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…Such an impairment in the degree of the airway obstruction and diffusion capacity was independent of the presence of COPD, as statistically significant differences were maintained among the three study clusters after excluding the COPD patients from the analysis in all three clusters. These results confirm that the differential phenotypes are associated with bronchiectasis per se rather than with COPD or the degree of the airflow limitation as also previously demonstrated [ 14 , 19 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Such an impairment in the degree of the airway obstruction and diffusion capacity was independent of the presence of COPD, as statistically significant differences were maintained among the three study clusters after excluding the COPD patients from the analysis in all three clusters. These results confirm that the differential phenotypes are associated with bronchiectasis per se rather than with COPD or the degree of the airflow limitation as also previously demonstrated [ 14 , 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…Phenotypic classification of bronchiectasis patients according to several clinical and biological markers may help predict disease severity, the risk of exacerbations, and disease prognosis. Recent investigations showed that a cut-off value greater than 5 reliably predicted hospitalizations and all-cause mortality according to the FACED (FEV 1 , age, chronic colonization, radiological extension, and dyspnea) and bronchiectasis severity index (BSI) scores [ 18 ] and that eosinophil levels defined differential clinical clusters of bronchiectasis patients [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrapulmonary manifestations are common among patients with chronic respiratory diseases, including those with bronchiectasis [ 5 , 6 , 7 , 8 ]. The analysis of skeletal muscle dysfunction and sarcopenia of patients with chronic obstructive pulmonary disease (COPD) have been a matter of research in multiple previous investigations [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This inflammation, along with various products of microorganisms (mainly bacterial proteolytic substances), is what ultimately causes the irreversible damage to the bronchial wall and airway dilation that characterize bronchiectasis and explain its symptoms [ 7 ]. Furthermore, a variable percentage of patients, especially those with greater severity, present a certain degree of systemic inflammation of a very heterogeneous nature [ 3 , 13 , 14 , 15 , 16 , 17 ], although some authors have found homogeneous groups based on parameters of cell or molecular counts in peripheral blood [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%